Cost–effectiveness of cetuximab combined with radiotherapy versus radiotherapy alone in locally advanced head and neck cancer in Spain - Ruth Alvarez Cabellos; Jon Cacicedo; Susana Redondo Capafons; Heidi De los Santos Real; Miriam Brines Julian; Dario Rubio-Rodriguez; Carlos Rubio-Terres (Journal of Comparative Effectiveness Research)
Aim: To estimate the cost–effectiveness of cetuximab in combination with radiotherapy compared with radiotherapy alone, for the treatment of locally advanced head and neck cancer patients in Spain. Methods: A probabilistic Markov model (second-order Monte Carlo simulation) with a five-year time horizon and quarterly Markov cycles was performed from the perspective of the Spanish National Health System (NHS). Results: The additional cost and quality-adjusted life-year (QALY) gain per patient receiving radiotherapy in combination with cetuximab compared with radiotherapy alone was €4356 (95% CI: €4350–4362) and 0.2380 (95% CI: 0.2370–0.2391) QALY, respectively. The incremental cost per QALY gain was €18,303 (95% CI: €18,243–18,354) with a probability of cost–effectiveness of 65.4% for a willingness to pay of €30,000 per QALY gained. Conclusion: According to the results of this analysis, the addition of cetuximab to radiotherapy would be a cost-effective alternative to radiotherapy alone in the treatment of locally advanced head and neck cancer in Spain.